Facile synthesis of nitrogen-doped graphene via low-temperature pyrolysis: The effects of precursors and annealing ambience on metal-free catalytic oxidation. (May 2017) - Li, Degang; Duan, Xiaoguang; Sun, Hongqi; Kang, Jian; Zhang, Huayang; Tade, Moses O.; Wang, Shaobin
Abstract: A green and facile protocol of thermal treatment of graphene oxide (GO) with urea was adopted to synthesize nitrogen-doped graphene (NG-Urea-air) at a low temperature (350 °C) in the static air. The resulting sample exhibited outstanding catalytic performance to activate peroxymonosulfate (PMS) toward organic degradation. The NG-Urea-air induced 49.7- and 11.5-fold enhancement over GO and pristine reduced graphene oxide (rGO-air). Moreover, the influences of nitrogen precursors including organic chemicals (urea, cyanamide, and melamine) and inorganic salts (ammonium nitrate and ammonium chloride) were investigated, and urea was demonstrated to be the best precursor for synthesizing N-doped graphene with a relative high doping level (18.7 at.%). The classical radical quenching and advanced in situ electron paramagnetic resonance (EPR) technology revealed that the outstanding oxidative effectiveness of PMS/NG-Urea-air system was originated from the nonradical oxidation pathway, in which PMS was activated by the positively charged carbon domains next to nitrogen atoms and the phenol was oxidized simultaneously on the carbon network via rapid charge transfer. Meanwhile, singlet oxygen and radicals may also partially contribute to the complete phenol degradation. This study facilitates a fundamental investigation of heteroatom doping progress during thermal treatment and sheds light on the insights into carbocatalysis in environmental remediation. Graphical abstract: